ANALISIS PERAN FORUM UMKM KECAMATAN SUNGAI PUA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Anisa Kamila Sari; Zulhelmi (Jurnal Ekonomi dan Bisnis, 2024)
This research was motivated by the problems experienced by MSME actors in Sungai Pua District. Among them is the lack of interest of MSME actors to join the MSME Forum of Sungai Pua District, business actors who do not want to legalize their business. Limited human resources, capital, tools and knowledge and marketing materials in developing their business.This study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. While data analysis uses data reduction, data presentation and conclusions according to Miles and Hulbes. The purpose of this study is to determine the role of the Sungai Pua Sub-District MSME Forum in an effort to improve community welfare and find out the obstacles faced by the Sungai Pua Sub-District MSME Forum in an effort to improve community welfare.The results showed that the role of the Sungai Pua Sub-District MSME Forum in an effort to improve community welfare is to conduct entrepreneurship training activities, MSME bazaars, aspiration forums, provide access to capital assistance and business legality assistance. And by carrying out the role as a stabilizer, pioneer innovator and modrensiator, namely providing access to capital assistance, socialization of types of capital assistance. Business legality assistance, marketing of MSME and pe products.